Perception of residents in relation to Arborization in the municipality of Ibateguara, Alagoas, Brazil - Maria José de Holanda Leite; Thamyres Valeriano Teixeira; Arrysson Cardoso da Silva; Cosme Ângelo da Silva (Universidade Estadual de Alagoas, 2020)
The improvement of quality of life in urban environments can occur through afforestation, which contributes to air purification, improvement of the city's climate by retaining soil and air moisture, by generating shadow, preventing solar rays from affecting directly on people. The aim of this research was to evaluate the positive and negative environmental impacts of urban arborization through the report of residents of the municipality of Ibateguara-AL. Thus, a semi-structured questionnaire was applied with fifteen questions about Arborization, Totaling 50 completed questionnaires. Through the results obtained, it was possible to observe that the residents, have empirical knowledge on the subject, where arborization is associated only with trees and shade, yet do not possess adequate knowledge about all the benefits of afforestation For its maintenance. These data reinforce the need for planning the afforestation of the municipality, with the implementation of an environmental education project, seeking to raise awareness of the population of its importance.